The Influence of Net Profit, Operating Cash Flow, Investment Cash Flow, Debt to Equity Ratio (DER) on Share Prices at Manufacturing Companies - Ragil Wahyu Utomo; Suhendro Suhendro (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study discusses the comparison of capital intensity, corporate advertising expenses and tax compensation against tax avoidance. Regression data panels using the commond effect (CE) method were used in solving this case. The data used in this study are secondary data derived from the company's financial statements. The study population is a banking sector company listed on the Indonesia Stock Exchange (IDX). The research sample is a banking sector company for the period 2015 - 2017 with a sampling technique that is purposive sampling. The sampling technique, obtained by the sample of 26 banking companies in the period 2015 - 2017 with a total sample of 78 banking financial statements. The results of the first hypothesis study indicate that the modality ratio has no effect on the dependent variable, namely tax avoidance. The second hypothesis which shows the burden of corporate advertising has no effect on the independent variable, namely tax avoidance, and the third hypothesis is the free variable compensation for tax money against the variable received, namely tax avoidance.